2019
DOI: 10.3390/su11051442
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Assessment of Seasonal Drought Risk to Crop Production in Bangladesh

Abstract: Droughts are more damaging when they occur during crop growing season. This research assessed the spatial distribution of drought risks to crops in Bangladesh. Catastrophe theory-based weighting method was used to estimate drought hazard, exposure, and risk by avoiding potential human bias. Ten major crops, including eight different types of rice, wheat, and potato, were selected for evaluation of drought risk. Results showed that 32.4%, 27.2%, and 16.2% of land in Bangladesh is prone to extreme Kharif (May-Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The historical data on frequency and intensity of floods and cyclones were collected from the Bangladesh Bureau of Statistics (BBS) report, and the hazard score was computed following the methodology of Barua et al (2016) [63]. The district-level average drought intensity score was obtained from Alamgir et al (2019) [64], calculated based on the time series precipitation data during 1994–2013 for the Kharif season.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The historical data on frequency and intensity of floods and cyclones were collected from the Bangladesh Bureau of Statistics (BBS) report, and the hazard score was computed following the methodology of Barua et al (2016) [63]. The district-level average drought intensity score was obtained from Alamgir et al (2019) [64], calculated based on the time series precipitation data during 1994–2013 for the Kharif season.…”
Section: Methodsmentioning
confidence: 99%
“…HR = Hypothesized relationship between the indicator and vulnerability dimensions; TP = Time Period; BMD = Bangladesh Meteorological Department; BBS = Bangladesh Bureau of Statistics; SRDI = Soil Resources Development Institute; HYV = High Yielding Variety; a See detailed methodology in Barua et al 2016; b See detailed methodology in supplementary information; * [64] Alamgir et al 2019.…”
Section: Figurementioning
confidence: 99%
“…Bangladesh is one of the most vulnerable countries in the world to climate change, including water-deficit stress. It was reported that in Bangladesh 32.4% of the land during May to October (Kharif season), 27.2% in November to April (Rabi season), and 16.2% between March to May (pre-Kharif season) are under the threat of extreme water shortage, respectively (Alamgir et al, 2019). The scientific community agrees that plant growth and yield is affected by water-deficit stress (Vurukonda et al, 2016;Chandra et al, 2018;Martins et al, 2018;Saikia et al, 2018;Meenakshi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has significant impacts on several sectors including agriculture, health, water resources, energy, and industry among others. Of these, the water resources sector will be the most affected by the variability of the climate, and this will subsequently impact other sectors [10][11][12][13] causing severe economic loses. The dynamism of climatic variables has been reported in many studies, particularly, changes in rainfall [14][15][16][17][18][19] and temperature [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%